2016
DOI: 10.1152/ajpheart.00247.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between AT1receptors and Toll-like receptor 4 in microglia contributes to angiotensin II-derived ROS production in the hypothalamic paraventricular nucleus

Abstract: II is thought to increase sympathetic outflow by increasing oxidative stress and promoting local inflammation in the paraventricular nucleus (PVN) of the hypothalamus. However, the relative contributions of inflammation and oxidative stress to sympathetic drive remain poorly understood, and the underlying cellular and molecular targets have yet to be examined. ANG II has been shown to enhance Toll-like receptor (TLR)4-mediated signaling on microglia. Thus, in the present study, we aimed to determine whether AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 92 publications
6
64
0
3
Order By: Relevance
“…11 As the main mediator of brain RAS over-activity, the AT 1a R was previously demonstrated to prompt ADAM17 up-regulation both in vitro 18 and in vivo. 5 Moreover, in recent years cell-specific expression of AT 1a R, in the CNS, has been shown to contribute to neurogenic hypertension 10,27,28 and other ailments. 29 Since AT 1a R and ADAM17 co-exist on various cell types, including endothelial cells, 30 vascular smooth muscle cells, 31 glial cells and neurons, 32 the contribution of cell-specific ADAM17 activation to the development of hypertension must be determined to insure selective targeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 As the main mediator of brain RAS over-activity, the AT 1a R was previously demonstrated to prompt ADAM17 up-regulation both in vitro 18 and in vivo. 5 Moreover, in recent years cell-specific expression of AT 1a R, in the CNS, has been shown to contribute to neurogenic hypertension 10,27,28 and other ailments. 29 Since AT 1a R and ADAM17 co-exist on various cell types, including endothelial cells, 30 vascular smooth muscle cells, 31 glial cells and neurons, 32 the contribution of cell-specific ADAM17 activation to the development of hypertension must be determined to insure selective targeting.…”
Section: Discussionmentioning
confidence: 99%
“…However, AT 1 R are expressed on various cell types in the brain, including neurons, microglia and astrocytes, which have been shown to contribute to neurogenic hypertension. [8][9][10] To further investigate the relationship between brain RAS and ADAM17 activation, we used the deoxycorticosterone acetate (DOCA)-salt model, which promotes RAS activation specifically in the brain, to test the hypothesis that neuronal AT 1a R are essential for ADAM17-mediated ACE2 shedding in neurogenic hypertension. 5,11 In patients, we observed an increase in sACE2, indicating increased ACE2 ectodomain shedding in hypertensive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, conducted in different models of hypertension, including the spontaneously hypertensive rat and the angiotensin II infusion model in Sprague–Dawley rats, have reported the presence of neuroinflammation, including increased production of pro‐inflammatory cytokines (Bardgett et al., ; Biancardi et al., ; Shi et al., ). A recent study conducted in the DSS rat model also reported an upregulation of PVN pro‐inflammatory cytokines in response to high dietary sodium intake (Jiang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes have also been demonstrated to mediate neuronal excitability and even influence the firing rates of neurons, potentially disrupting neural homeostasis (Galic, Riazi, & Pittman, 2012;Shi et al, 2011). Glial cells, including microglia and astrocytes, can become activated in response to a pathological stimulus and have been demonstrated to produce inflammatory cytokines and reactive oxygen species and to disrupt neural homeostasis (Biancardi, Stranahan, Krause, de Kloet, & Stern, 2016;Wolf, Boddeke, & Kettenmann, 2017). Therefore, we hypothesized that central inflammatory processes, involving activation of microglia and astrocytes, contribute to the development of G i 2 protein-dependent, salt-sensitive hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that isolated hypothalamic microglia actually respond to Ang II through AT1 and TLR4 receptors, the latter which is required for the expression of oxidative damage induced by Ang II in mice [49]. Although the role of other cells including neurons and astrocytes cannot be discarded, the ultrastructural morphological changes along with the increased hippocampal TNF-α production suggest the emergence of a pro-inflammatory microglial phenotype in mice with chronic Ang II administration.…”
Section: Discussionmentioning
confidence: 99%